Measuring blood pressure in small animal patients - Carr, Anthony (Henry Stewart Talks, 2019)
Signs that you should measure blood pressure in small animal patients, Hypertension in small animal practice, and its association with endocrine and renal diseases, Targets of hypertension, The pros and cons of Doppler and Oscillometric blood pressure monitors, The benefits of observing oscillometric tracing, The impact of white coat effect on blood pressure and how to minimize it